COMPARISON OF THE EFFICACY OF SINGLE VOLAR SUBCUTANEOUS DIGITAL BLOCK AND THE DORSAL TWO INJECTIONS BLOCK - Afridi, Riaz Ahmed Khan; Masood, Tariq; Ahmed, Ehtisham; Jaffar, Abdul Majeed; ullah, Obaid; Alvi, Hamid Fazeel (Journal of Ayub Medical College Abbottabad, 2014)
Background: Digital nerve blocks are commonly used as effective techniques of anaesthesia to allow a variety of surgical procedures performed on digits. This study was conducted to compare the efficacy of volar subcutaneous single injection block and the traditional dorsal two injections digital block. Methods: This randomized controlled trial was conducted at Plastic and Reconstructive Surgery Department, Hayatabad Medical Complex Peshawar from December. 2009-10. A total of 126 patients with pathology distal to the first palmer digital crease divided into two equal groups. Group A received volar subcutaneous digital block while group B dorsal two injections block. Efficacy of digital block was measured in terms of time of onset of anaesthesia, which was the total time duration after administering local anaesthetic to loss of pinprick sensation and total duration of anaesthesia, which was defined as the time period from onset of block (loss of pinprick sensation) till the appearance of pain which required additional local anaesthetic or postoperative analgesia. Results: A total of 126 patients were studied, 63 in each group. Of the total patients, 102 (81%) were male and 24 (19%) female with a mean age of 27±4.2 years (range 17-60 years). The mean time of onset of anaesthesia from injection till the loss of pin prick sensation was 3.32±0.42 minutes for volar single injection group and 4.53 minutes±0.57 minutes for dorsal two injections group (p=0.049). Similarly the mean total duration of anaesthesia for the volar subcutaneous group was 271.9±29.34 minutes while for the dorsal two injections group, it was 229.52±28.82 minutes (p=0.415). Conclusion: Single injection volar subcutaneous digital block provides faster onset of anaesthesia, produces predictable, consistent dense anaesthesia of all of the fingers with the help of single injection prick. Keywords: Volar digital block, dorsal digital block, local anaesthesia